Nutrition and dietetics practice and future trends - Winterfeldt, Esther A.; Bogle, Margaret L.; Ebro, Lea L. (Jones & Bartlett Learning, 2014)
This text provides an overview of the career opportunities for dietitians, explaining what they do, highlighting the specific areas of dietetic practice, and listing the requirements to become a dietitian